Disparitas Putusan Hakim dalam Penetapan Rujuk Bil Fi’li Pasca Cerai Talak - Saiful Alam, Zaki (Prodi Ahwal Al-Syakhsiyyah STAI Imam Syafi'i Cianjur, 2024)
This article analyzes the difference in decisions between religious court panels in divorce cases. The Bandung Religious High Court rejected the Bogor Religious Court's divorce verdict, then the Supreme Court rejected the Bandung Religious High Court's verdict. The Bogor Religious Court decided that divorce is the last alternative so that each party does not further violate legal and religious norms. One of the reasons for the Bandung High Court's rejection was the existence of rujuk bil fi'li (rujuk by action), namely intercourse. The applicant reapplied for divorce to the cassation level by bringing evidence so that it was granted by the Supreme Court and gave the applicant permission to impose the pledge of divorce with decision number 394 K/Ag/2015. This article uses a case study approach with descriptive analytical research methods, then analyzes the data using the perspective of Law No. 1 Th. 1974 on marriage, Qawaid Fiqhiyyah and Jeremy Bentham's Utilitarianism theory. This study argues that the Supreme Court's decision is correct, because it is in accordance with Law No. 1 of 1974 concerning marriage, Qawaid Fiqhiyyah and the Compilation of Islamic Law. The Supreme Court used the opinion of the Syafi'iyah school of thought which states that rujuk bil fi'li is not allowed and having intercourse during the 'iddah period is prohibited. KHI has regulated rujuk and does not accommodate the opinion of the fiqh experts who justify rujuk bil fi'li.